Reality aftershock and how to avert it: second-year teachers' experiences of support for their professional development - J.Hobson, Andrew; Ashby, Patricia (Cambridge journal of education, 2012)
Drawing on analyses of data from a large-scale, mixed-method study of new entrants to the teaching profession in England, this article presents new findings on beginner teachers' experiences of post-induction support for their professional development, about which little was previously known. As well as highlighting positive and negative aspects of support provision, it is shown that the recognised phenomenon of 'reality shock' is not confined to the transition between initial teacher preparation and teachers' first year in post, since some second-year teachers experience a new or additional shock associated with the cessation of the induction support introduced, in part, to cushion the impact of that transition. Amongst the potential implications of these findings, it is argued that where they do not already exist, formal mechanisms should be introduced to facilitate the provision of contingent support for beginner teachers' professional development beyond their first year.